Evaluation of the Production-Education Integration Performance of the High-Tech Industry: An Empirical Comparison between Three Urban Agglomerations in China - Quan Zhang; Zhen Zhang; Zhuomei Li; Sifeng Li; Tianzhen Tang (Discrete Dynamics in Nature and Society)
Deepening production-education integration (PEI) is a major strategy of China to reinforce education reform and promote industry transformation. Different from the traditional research perspective of colleges on the supple side, this paper chooses to evaluate the PEI performance of the high-tech industry from the angle of industry on the demand side. Firstly, the action mechanisms of the education system and industry system in PEI were expounded, and the design framework of the evaluation index system (EIS) was derived from the interactions between two elements (technologies and talents) and two market relationships (supply and demand), forming a two-dimensional four-quadrant EIS. On this basis, the correlation-entropy composite matter-element (CECME) model and coupling coordination degree (CCD) model were introduced to empirically compare the PEI performance of the high-tech industry between Guangdong-Hong Kong-Macao (GHKM) Greater Bay Area, Beijing-Tianjin-Hebei (BTH) Urban Agglomeration, and Yangtze River Delta (YRD) Urban Agglomeration. The main conclusions are as follows: (1) the GHKM Greater Bay Area is far better in education and industry development than YRD Urban Agglomeration and BTH Urban Agglomeration; (2) the PEI performance of the high-tech industry in GHKM Greater Bay Area was evaluated as high level with industry in lead, that in YRD Urban Agglomeration as moderate level with education in lead, and that in BTH Urban Agglomeration high-tech industry PEI as moderate level with industry in lag. Finally, several countermeasures were proposed for the urban agglomerations to further enhance the PEI performance of the high-tech industry: GHKM Greater Bay Area should improve the weak link of education development; YRD Urban Agglomeration should give full play to its advantages in higher education; BTH Urban Agglomeration should focus on high-quality industry development. From the practical level, this paper objectively evaluates the actual performance of PEI and provides a reference for scientific policymaking of PEI development.